Upaya Non-Penal Polisi dalam Penanggulangan Pelanggaran Kecepatan di Polres Oku - Julianna, Alya Putri; Dewi, Erna; Shafira, Maya; Raharjo, Eko; Ginting, Mamanda Syahputra (Jurnal Studi Pemerintahan dan Akuntabilitas, 2025)
Purpose: This study aimed to assess the effectiveness of non-penal measures implemented by the police in preventing and reducing speed limit violations, particularly illegal street racing (balap liar), in Baturaja Barat District, South Sumatra. This study also aims to explore in depth the role of the police in addressing speed limit violations, focusing on how law enforcement can effectively carry out duties to reduce such offenses. This includes various aspects, such as the implementation of preventive measures involving public outreach, awareness campaigns about the dangers of violating speed limits, and the use of technology in monitoring and enforcing the law.   Methodology: This study used an empirical research method by conducting interviews at the Baturaja Barat Police Station and Polres OKU. Results: Routine patrols, school socialization campaigns, and parental involvement have successfully reduced illegal street racing incidents between June and October 2024. Conclusion: The role of the police in tackling illegal racing includes normative and factual efforts, with an emphasis on non-penal approaches such as education and parental involvement. The main obstacles stem from low legal awareness, weak sanctions, lack of legal facilities, and social and cultural factors. Limitations: There are still limitations in resources, lack of parental awareness, and absence of legal racing venues. Contribution: Provides insights for policymakers and law enforcement to develop preventive, educative, and rehabilitative non-penal strategies in dealing with illegal racing to increase collective awareness of road safety and reduce accidents due to speed limit violations.